Factor structure and psychometric properties of the Chinese version of the Intuitive Exercise Scale for young adults - Shi, Dongzhe; Lv, Fangyan; Tan, Jingbin; Gao, Dingguo (Frontiers in Psychology, 2025)
BackgroundThe Intuitive Exercise Scale (IEXS) is a scale designed to evaluate the positive relationship with exercise, including their ability to tune in to bodily cues, maintain mindfulness while moving, and utilize diverse movement patterns. As that the psychometric properties of the IEXS have not been thoroughly established across cultures and various age groups, the purpose of this study is to evaluate the applicability of the translated IEXS among young Chinese adults.MethodsWe translated and culturally adapted the IEXS for a sample of 630 Chinese young adults (M = 19.61 SD = 1.13) who agreed to complete the scale online. The psychometric evaluation included item analysis, exploratory and confirmatory factor analysis (EFA and CFA), and assessments of reliability, predictive validity, and criterion validity.ResultsThe mean IEXS score was 47.23 (SD = 7.28), and EFA identified four latent constructs: emotional exercise, exercise rigidity, body trust, and mindful exercise. The CFA confirmed the model’s fit (CFI = 0.98; SRMR = 0.06). Item-total correlations ranged from 0.639 to 0.753, with item loadings between 0.635 and 0.760. Also, the reliability metrics demonstrated strong internal consistency (Cronbach’s α = 0.869) and test–retest stability (ICC = 0.721, p < 0.01). Predictive validity was confirmed through significant correlations with the Physical Activity Rating Scale (PARS-3), and criterion validity showed moderate correlations (0.342–0.615) with validated scales.ConclusionThe Chinese IEXS is a robust and valid tool for assessing intuitive exercise tendencies in Chinese young adults.